Management Prospects for COVID-19: A Review - Jilani, Uzma Aamir; Rahman, Ishrat; Jilani, Syed Aamir (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
Although the number of active COVID-19 cases have been fallen in some countries, the threat of the pandemic is still impending in many parts of the world and the pace of recovery is still uncertain. SARS-CoV-2 outbreak has expanded very quickly since the beginning of 2020 and has now taken approximately a million lives all around the globe. Sadly, there is yet to be an approved treatment for COVID-19 as it may take a few years to establish a definitive treatment and a vaccine against SARS-CoV-2. This study aims to review the preventive and curative measures currently under investigation for COVID-19 and the targeted pathogenic features of the SARS-CoV-2. To manage the clinical implications of COVID-19, and to alleviate SARS-CoV-2, the main focus is on supportive therapy, symptom control, antiviral drugs, and immunomodulation. Intense research activities for therapeutic interventions are in progress worldwide to evaluate the benefit of such drugs.